Faktor Yang Berhubungan Dengan Perilaku Mengkonsumsi Minuman Beralkohol Remaja Di Desa Lakanmau Kecamatan Lasiolat Belu - Manek, Leopoltus D.; Takaeb, Afrona E. L.; Regaletha, Tadeus A. L. (Faculty of Public Health, Nusa Cendana University, 2019)
The behavior in the consumption of alcoholic beverages is one of the main problems among young people in the village of Lakanmau. The aim of this study was to determine the factors related to the consumption behavior of alcoholic drinks in adolescents in the village of Lakanmau in 2018. The research used was an analytical survey using a cross-sectional design. The population in this study was the total population of adolescents aged 12 to 21 years in the Lakanmau Village area with 182 adolescents. The sample size was 65 respondents. There was data analysis used a chi-square test at a confidence level of 90%. The results showed that a correlation between the knowledge level (P-Value = 0.001<0.05), the educational level (P-Value = 0.000<0.05) and the invitation of peers (P-Value = 0.002<0.05) and the behavior consists adolescents consume alcoholic beverages in the village of Lakanmau. It is recommended for parents to give the good controlling for their children about the consumption of alcohol beverages.